Estudio ultraestructural del diafragma desnervado en ratas - Torrejais, M. M. (2013)
The structural alterations that occur in the muscle fibers of denervated rat diaphragms were studied. Fifteen adult male albino rats (Rattus norvegicus) with a mean weight of 200 g and about 60 days of age were used. Chronically denervated diaphragms were obtained and the animals were sacrificed after 4, 8 and 12 weeks of denervation. The left antimere of the diaphragm was denervated by sectioning of the phrenic nerve and the right antimere served as control. Each antimere was divided into fragments, which were used for analysis transmission electron microscopy. During the initial phase of denervation (4 weeks), ultrastructural muscle modifications appeared in scattered fibers and in foci along these fibers. Muscle fibers with foci of less dense and loosely arranged myofibrils, disorganized Z line, displaced T tubules, and central nucleus exhibiting reentrances and fragmented aspect were observed. After 8 weeks, formation of large aggregates of small elongated mitochondria showing altered cristae, matrix inclusions and increased electron density was noted. At 12 weeks of denervation the alterations were found to be more drastic. Nuclei with internal deposits of myofibrillar or amorphous material were observed. In these fibers, vacuoles harbored enormous myeloid structures in the subsarcolemmal or intermyofibrillar region.